Method for preparing nanoscale neodymium iron boron permanent magnet material by aerosol jet printing technology

The preparation of nano-grade neodymium iron boron permanent magnet materials through aerosol jet printing technology has solved the problems of insufficient performance, low efficiency and environmental pollution in the existing technology, and achieved efficient, low-cost and environmentally friendly nano-grade magnetic powder preparation, which is suitable for industrial production.

CN119920614AActive Publication Date: 2025-05-02JIANGXI UNIV OF SCI & TECH +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510424039.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-07
Publication Date
2025-05-02
Estimated Expiration
2045-04-07

AI Technical Summary

Technical Problem

The prior art has problems such as insufficient performance, low efficiency, limited output, high raw material costs and serious environmental pollution when preparing nano-scale neodymium iron boron permanent magnet materials, which is difficult to meet the needs of industrial production.

Method used

Aerosol jet printing technology is adopted to dissolve metal salt and boric acid in deionized water, mix evenly and aged to form sol ink, and spray printing on the substrate through an aerosol jet printing device, and then annealed under a mixed atmosphere of hydrogen and argon to obtain nano-scale neodymium iron boron permanent magnet material.

Benefits of technology

It has achieved the preparation of uniform, controllable size and high magnetic properties of nano-grade neodymium iron boron permanent magnet materials, which reduces annealing temperature, reduces chlorine residues, improves production efficiency and economy, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119920614A_ABST
    Figure CN119920614A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a nanoscale neodymium iron boron permanent magnet material through an aerosol jet printing technology. The nanoscale neodymium-iron-boron permanent magnet material is prepared by combining an aerosol technology with a sol-gel method, the method is simple, the implementation difficulty is low, raw materials are mixed more sufficiently in a liquid phase, complexation reaction is promoted, and a stable and uniform sol system is formed. Along with the propulsion of the gelation process, the formed spatial network structure also effectively controls the particle size, the performance consistency and excellent controllability of the obtained magnetic material are ensured, the prepared magnetic powder particles are uniform, the size is controllable, the magnetic performance is relatively high, the annealing temperature is greatly reduced, and the production cost is reduced. And a breakthrough path is provided for industrial production of the high-performance NdFeB permanent magnet nanoparticles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of magnetic materials, in particular to a method for preparing nano-grade NdFeB permanent magnetic materials by using aerosol jet printing technology. Background Art

[0002] Rare earth permanent magnet materials have a wide range of applications and show a very broad market potential. Neodymium iron boron (NdFeB) permanent magnet material is a rare earth permanent magnet material. So far, research in this field has mainly focused on the development of sintered and bonded NdFeB and more rare earth permanent magnet materials. Whether it is the preparation of bonded magnets, sintered magnets, or magnetic elastomers, magnetic powder is an indispensable foundation.

[0003] The main physical preparation methods of NdFeB magnetic powder are powder metallurgy and rapid quenching. The production of conventional micron-level NdFeB magnetic powder relies on spin quenching, crushing, ball milling and HDDR (Hydrogen Disproportionation Desorption and Reconstruction) technology, but these technologies have high energy consumption and require high purity of the initial raw materials. Nanoscale permanent magnetic nanoparticles have shown application potential in anisotropy, exchange coupling, single-domain particles, ferrofluids, cooling systems and high-density storage due to their unique morphology and size distribution. It is well known that chemical synthesis has its unique advantages in the preparation of nanomaterials. At present, the chemical preparation methods mainly include the use of sodium borohydride to reduce neodymium salts and iron salts, and the use of polyol reduction method. However, due to the high electrode potential of rare earth elements and the easy oxidation of NdFeB alloys, the effective and environmentally friendly preparation of nanoparticles faces great challenges.

[0004] The document with application number 201410181298.0 discloses a method for preparing NdFeB permanent magnetic nanoparticles, which uses Nd acetylacetonate, Fe acetylacetonate and ethyl borate as raw materials to avoid the difficulty in removing the chlorine element introduced when using Nd chloride hexahydrate, Fe chloride hexahydrate and boric acid as raw materials, thereby affecting the performance of the product and causing harm to production equipment and personnel. However, this increases the cost of raw materials and reduces economic applicability.

[0005] In view of this, the traditional preparation method of NdFeB permanent magnetic nanoparticles exposes problems such as insufficient product performance, low efficiency, limited output, high raw material costs, limited choices and serious environmental pollution. There is an urgent need for a new method that is efficient, high-yield, low-cost and environmentally friendly to meet the needs of industrial production. Summary of the invention

[0006] In view of the deficiencies in the prior art, the technical problem to be solved by the present invention is to provide a method for preparing nano-grade NdFeB permanent magnet material by using aerosol jet printing technology.

[0007] The technical solution of the present invention to solve the technical problem is to provide a method for preparing nano-grade NdFeB permanent magnet material by aerosol jet printing technology, characterized in that the method comprises the following steps: Step 1, dissolving a metal salt and boric acid in deionized water to obtain a mixed solution; the metal salt comprises neodymium chloride hexahydrate and ferric chloride hexahydrate; Step 2, uniformly mixing the citric acid / ethylene glycol aqueous solution with the mixed solution obtained in step 1 to obtain a sol ink mother solution; Step 3, aging the sol ink mother liquor obtained in step 2 to obtain a sol; Step 4, uniformly mixing the organic dispersant, deionized water and the sol obtained in step 3 to adjust the viscosity of the system, and then adjust the atomization stability of the sol to obtain a sol ink; Step 5, atomizing the sol ink obtained in step 4 to form droplets, and conveying them to an aerosol jet printing device; the droplets are conveyed to the printing nozzle by a carrier gas; the carrier gas, the constraining gas and the droplets together form an aerosol jet and are ejected from the printing nozzle; the aerosol jet is ejected onto the substrate through a heating device for aerosol jet printing to obtain oxide gel powder; Step 6, annealing the oxide gel powder obtained in step 5 in a mixed atmosphere of hydrogen and argon to perform a reduction reaction to obtain a micro-nano grade NdFeB permanent magnet material; Step 7: Disperse the micro-nano NdFeB permanent magnet material obtained in step 6 into an insoluble solvent, sieve it with a nano-scale filter membrane, continue to rinse until the filtrate is clear, and dry the filtrate to obtain the nano-scale NdFeB permanent magnet material.

[0008] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention adopts aerosol technology combined with sol-gel method to prepare nano-grade NdFeB permanent magnet materials. The method is simple and easy to implement. The raw materials in the liquid phase are mixed more fully, which promotes the complexation reaction and forms a stable and uniform sol system. As the gelation process progresses, the formed spatial network structure also effectively controls the particle size, ensuring the performance consistency and excellent controllability of the obtained magnetic material. The prepared magnetic powder particles are uniform, the size is controllable, and the magnetic properties are high. The temperature during annealing is greatly reduced, which provides a breakthrough path for the industrial production of high-performance NdFeB permanent magnet nanoparticles.

[0009] (2) The present invention innovatively combines aerosol technology, which makes the sol particle size smaller and significantly increases the specific surface area, thereby increasing the size uniformity and magnetic properties of the magnetic powder.

[0010] (3) The aerosol particles produced by aerosol technology are small in size and have large surface energy, which reduces the activation energy during high-temperature reactions and thus greatly reduces the temperature during annealing reduction.

[0011] (4) The present invention solves the problem of excessive residual chlorine in the product when using neodymium chloride hexahydrate, ferric chloride hexahydrate and boric acid as raw materials, thereby affecting the magnetic properties of nano-grade NdFeB magnetic powder, through aerosol technology. The heating device in the aerosol technology allows the residual chlorine to be removed by the constrained gas, resulting in less residual chlorine, thereby reducing costs and making it more suitable for industrialization.

[0012] (5) The present invention controls the size of the aerosol by adjusting the flow rates of the carrier gas and the confining gas in the aerosol technology, thereby regulating the size and microscopic morphology of the nano-scale NdFeB magnetic powder prepared by this method. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 This is a hysteresis loop diagram of the nano-grade NdFeB permanent magnet material prepared in Example 1 of the present invention; Figure 2 This is a SEM image of the nano-grade NdFeB permanent magnet material prepared in Example 1 of the present invention; Figure 3 This is a hysteresis loop diagram of the nano-grade NdFeB permanent magnet material prepared in Example 2 of the present invention; Figure 4 This is a SEM image of the nano-grade NdFeB permanent magnet material prepared in Example 2 of the present invention; Figure 5 This is a hysteresis loop diagram of the nano-grade NdFeB permanent magnet material prepared in Example 3 of the present invention; Figure 6 This is a hysteresis loop diagram of the nano-grade NdFeB permanent magnet material prepared in Example 4 of the present invention; Figure 7 This is the hysteresis loop diagram of the nano-grade NdFeB permanent magnet material prepared in Example 5 of the present invention. DETAILED DESCRIPTION

[0014] The specific embodiments of the present invention are given below. The specific embodiments are only used to further illustrate the present invention in detail and do not limit the protection scope of the present invention.

[0015] The present invention provides a method for preparing nano-grade NdFeB permanent magnet material by aerosol jet printing technology (hereinafter referred to as the method), characterized in that the method comprises the following steps: Step 1, dissolving a metal salt and boric acid in deionized water to obtain a mixed solution; the metal salt comprises neodymium chloride hexahydrate and ferric chloride hexahydrate; Preferably, in step 1, the ratio of the elements neodymium, iron and boron is as follows: 15 Fe 77.5 B 7.5The amount of substance of the nominal component in the chemical formula is added; the chloride ion concentration is 3~10mol / L.

[0016] Step 2, uniformly mixing the citric acid / ethylene glycol aqueous solution with the mixed solution obtained in step 1 to obtain a sol ink mother solution; Preferably, in step 2, the molar ratio of citric acid, ethylene glycol and metal salt is 2-50:2-50:1; and the volume ratio of citric acid / ethylene glycol aqueous solution to the mixed solution is 1:1.

[0017] Preferably, in step 2, the mixing is carried out uniformly by stirring; the stirring process is: a rotation speed of 100-1000 r / min, a temperature of 0-40° C., and a time of 10-60 min.

[0018] Step 3, aging the sol ink mother liquor obtained in step 2 to obtain a sol; Preferably, in step 3, the aging time is 12 to 72 hours, and the aging temperature is room temperature; aging allows citric acid, ethylene glycol and metal ions to be more thoroughly complexed, thereby ensuring that the sol particles are generated more thoroughly and are more uniform in the solution.

[0019] Step 4, uniformly mixing the organic dispersant, deionized water and the sol obtained in step 3 to adjust the viscosity of the system, and then adjust the atomization stability of the sol to obtain a sol ink; Preferably, in step 4, the volume ratio of deionized water to sol is 1-10:1-5, and the ratio of the mass of the organic dispersant to the volume of the sol is 1 g:100-1000 ml.

[0020] Preferably, in step 4, the organic dispersant is one of polyvinyl alcohol, polyvinyl pyrrolidone, polyethylene glycol, polyacrylic acid or gum arabic.

[0021] Preferably, in step 4, the mixing is carried out uniformly by stirring; the stirring process is: a rotation speed of 100-1000 r / min, a temperature of 0-40° C., and a time of 10-60 min.

[0022] Preferably, in step 4, the viscosity of the sol ink is 1-20 cP.

[0023] Step 5, atomizing the sol ink obtained in step 4 to form droplets, and conveying them to an aerosol jet printing device through an air pipe; the droplets are conveyed to a printing nozzle through a carrier gas; the carrier gas, the constrained gas and the droplets together form an aerosol jet that is ejected from the printing nozzle, and the flow rates of the carrier gas and the constrained gas are changed to adjust the width and injection speed of the aerosol jet; the aerosol jet is sprayed onto a substrate through a heating device, and the solvent evaporation behavior of the aerosol jet in the air is adjusted by changing the printing height and the temperature of the heating device, and the oxidation process of the aerosol on the substrate is adjusted by changing the printing speed, the number of printing layers and the temperature of the substrate to obtain an oxide gel powder; Preferably, in step 5, the atomization process is ultrasonic atomization, and the ultrasonic frequency is 1.5-2.5 MHz.

[0024] Preferably, in step 5, the flow rate of the carrier gas is 200-500 sccm, and the flow rate of the confinement gas is 50-150 sccm.

[0025] Preferably, in step 5, both the carrier gas and the confinement gas are nitrogen or an inert gas, and the inert gas is argon.

[0026] Preferably, in step 5, the printing height is 5-10 mm, the temperature of the heating device is 150-350° C.; the printing speed is 5-50 mm / s, the number of printing layers is 50-500 layers, and the temperature of the substrate is 40-180° C.

[0027] Preferably, in step 5, the substrate is a glass plate, a ceramic plate or a plastic plate.

[0028] Step 6, annealing the oxide gel powder obtained in step 5 in a mixed atmosphere of hydrogen and argon to perform a high-temperature reduction reaction, and obtaining a micro-nano grade NdFeB permanent magnet material after cooling; Preferably, in step 6, the reduction reaction temperature is 550-700° C. and the time is 3-6 hours.

[0029] Preferably, in step 6, the volume ratio of hydrogen to argon is 1-25:75-99 (preferably 5:95), and the sum of the volume ratios of the two is 100%.

[0030] Step 7: Disperse the micro-nano NdFeB permanent magnet material obtained in step 6 into an insoluble solvent, sieve it with a nano-scale filter membrane, continue to rinse until the filtrate is clear, and dry the filtrate to obtain the nano-scale NdFeB permanent magnet material.

[0031] Preferably, in step 7, the insoluble solvent is a solvent that cannot dissolve the micro-nano grade NdFeB permanent magnet material, specifically DMF, acetone or tetrahydrofuran.

[0032] Preferably, in step 7, the pore size of the nanoscale filter membrane is 0.05-0.22 μm.

[0033] Preferably, in step 7, the drying temperature is 60-100° C., and the drying time is 0.5-24 h.

[0034] Example 1: (1) Neodymium chloride hexahydrate, ferric chloride hexahydrate and boric acid were mixed according to Nd 15 Fe 77.5 B 7.5 The amount of the substance of the nominal component in the chemical formula is dissolved in 100 ml of deionized water, and the chloride ion concentration in the mixed solution is controlled to be 5 mol / L; a mixed solution is obtained; (2) 100 ml of citric acid / ethylene glycol aqueous solution was mixed evenly with the above mixed solution, with the stirring speed at 200 r / min, the temperature at 15°C, and the time at 15 min, and the molar ratio of citric acid:ethylene glycol:metal salt was controlled to be 2:2:1, to obtain a sol ink mother liquor; (3) aging the above sol ink mother solution at room temperature for 24 hours to obtain a sol; (4) Add 200 ml of deionized water to the above sol, add 0.4 g of polyvinyl alcohol to adjust the atomization stability, stir evenly, stir at a speed of 200 r / min, a temperature of 15°C, a time of 15 min, adjust the viscosity to 5 cP, and obtain a sol ink; (5) The above sol ink is atomized to form droplets, and the ultrasonic frequency is 1.9 MHz; the droplets are transported to the printing nozzle through a carrier gas, and the carrier gas, the constraining gas and the droplets together constitute an aerosol jet. The flow rate of the carrier gas is set to 350 sccm and the flow rate of the constraining gas is set to 75 sccm to control the width and injection speed of the aerosol jet. The aerosol jet is sprayed onto a 50°C substrate through a 200°C heating device, and the printing height is 5 mm. The solvent evaporation rate of the aerosol jet in the air is controlled, and the printing speed is set to 10 mm / s and the number of printing layers is 100 layers to control the oxidation process of the aerosol on the substrate to obtain oxide gel powder; nitrogen is used for both the carrier gas and the constraining gas; (6) annealing the oxide gel powder in a mixed atmosphere of hydrogen and argon (the volume ratio of hydrogen to argon is 5:95) to perform a reduction reaction at a reduction temperature of 675°C for 3.5 hours, and obtaining a micro-nano NdFeB permanent magnet material after cooling; (7) Disperse the micro-nano NdFeB permanent magnet material in DMF, sieve it with a nano-scale filter membrane, and continue to rinse until the filtrate is clear. After drying the filtrate at 60°C for 24 hours, the nano-scale NdFeB permanent magnet material is obtained.

[0035] Depend on Figure 1 It can be seen that the saturation magnetization intensity of the obtained nano-scale NdFeB permanent magnet material is 63.4emu / g, the residual magnetization intensity is 21.8emu / g, and the coercive force is 1874Oe.

[0036] Depend on Figure 2 It can be seen that the obtained nano-grade NdFeB permanent magnet material is magnetic powder, and its shape is ellipsoidal.

[0037] Example 2: (1) Neodymium chloride hexahydrate, ferric chloride hexahydrate and boric acid were mixed according to Nd 15 Fe 77.5 B 7.5 The amount of the substance of the nominal component in the chemical formula is dissolved in 200 ml of deionized water, and the chloride ion concentration in the mixed solution is controlled to be 3 mol / L; a mixed solution is obtained; (2) 200 ml of citric acid / ethylene glycol aqueous solution was mixed evenly with the above mixed solution, with the stirring speed being 400 r / min, the temperature being 25° C., and the time being 30 min, and the molar ratio of citric acid:ethylene glycol:metal salt being controlled to be 50:50:1, to obtain a sol ink mother liquor; (3) aging the above sol ink mother solution at room temperature for 48 hours to obtain a sol; (4) Add 80 ml of deionized water to the above sol, add 2.4 g of polyvinyl pyrrolidone to adjust the atomization stability, stir evenly, stir at a speed of 400 r / min, a temperature of 25° C., and a time of 30 min, and adjust the viscosity to 3 cP to obtain a sol ink; (5) The above sol ink is atomized to form droplets, and the ultrasonic frequency is 2.3 MHz; the droplets are transported to the printing nozzle through the carrier gas, and the carrier gas, the constraining gas and the droplets together constitute an aerosol jet. The flow rate of the carrier gas is set to 500 sccm and the flow rate of the constraining gas is set to 150 sccm to control the width and injection speed of the aerosol jet. The aerosol jet is sprayed onto an 80°C substrate through a 250°C heating device, and the printing height is 7 mm. The solvent evaporation rate of the aerosol jet in the air is controlled, and the printing speed is set to 20 mm / s and the number of printing layers is 150 layers to control the oxidation process of the aerosol on the substrate to obtain oxide gel powder; argon is used as the carrier gas and the constraining gas; (6) annealing the oxide gel powder in a mixed atmosphere of hydrogen and argon (the volume ratio of hydrogen to argon is 5:95) to perform a reduction reaction at a reduction temperature of 600° C. for 6 hours, and obtaining a micro-nano NdFeB permanent magnet material after cooling; (7) Disperse the micro-nano NdFeB permanent magnet material in acetone, sieve it with a nano-scale filter membrane, and continue to rinse until the filtrate is clear. After drying the filtrate at 80°C for 10 hours, the nano-scale NdFeB permanent magnet material is obtained.

[0038] Depend on Figure 3 It can be seen that the saturation magnetization intensity of the obtained nano-scale NdFeB permanent magnet material is 61.9emu / g, the residual magnetization intensity is 20.7emu / g, and the coercive force is 1765Oe.

[0039] Depend on Figure 4 It can be seen that the obtained nano-grade NdFeB permanent magnet material is magnetic powder, and its shape is ellipsoidal.

[0040] Example 3: (1) Neodymium chloride hexahydrate, ferric chloride hexahydrate and boric acid were mixed according to Nd 15 Fe 77.5 B 7.5 The amount of the nominal component in the chemical formula is dissolved in 500 ml of deionized water, and the chloride ion concentration in the mixed solution is controlled to be 8 mol / L; a mixed solution is obtained; (2) 500 ml of citric acid / ethylene glycol aqueous solution was mixed evenly with the above mixed solution, with the stirring speed being 600 r / min, the temperature being 40° C., and the time being 40 min, and the molar ratio of citric acid:ethylene glycol:metal salt being controlled to be 25:25:1, to obtain a sol ink mother liquor; (3) aging the above sol ink mother solution at room temperature for 72 hours to obtain a sol; (4) Add 2 L of deionized water to the above sol, add 10 g of polyacrylic acid to adjust the atomization stability, stir evenly, stir at a speed of 600 r / min, a temperature of 40° C., and a time of 40 min, and adjust the viscosity to 10 cP to obtain a sol ink; (5) The above sol ink is atomized to form droplets, and the ultrasonic frequency is 1.7 MHz; the droplets are transported to the printing nozzle through a carrier gas, and the carrier gas, the constraining gas and the droplets together constitute an aerosol jet. The flow rate of the carrier gas is set to 250 sccm and the flow rate of the constraining gas is set to 125 sccm to control the width and injection speed of the aerosol jet. The aerosol jet is sprayed onto a 120°C substrate through a 275°C heating device, and the printing height is 6.5 mm. The solvent evaporation rate of the aerosol jet in the air is controlled, and the printing speed is set to 25 mm / s and the number of printing layers is set to 200 layers to control the oxidation process of the aerosol on the substrate to obtain oxide gel powder; nitrogen is used for both the carrier gas and the constraining gas; (6) annealing the oxide gel powder in a mixed atmosphere of hydrogen and argon (the volume ratio of hydrogen to argon is 5:95) to perform a reduction reaction at a reduction temperature of 550° C. for 5 h, and obtaining a micro-nano NdFeB permanent magnet material after cooling; (7) Disperse the micro-nano NdFeB permanent magnet material in acetone, sieve it with a nano-scale filter membrane, and continue to rinse until the filtrate is clear. After drying the filtrate at 100°C for 1 hour, the nano-scale NdFeB permanent magnet material is obtained.

[0041] Depend on Figure 5 It can be seen that the saturation magnetization intensity of the obtained nano-scale NdFeB permanent magnet material is 58.9emu / g, the residual magnetization intensity is 22.3emu / g, and the coercive force is 1803Oe.

[0042] Example 4: (1) Neodymium chloride hexahydrate, ferric chloride hexahydrate and boric acid were mixed according to Nd 15 Fe 77.5 B 7.5 The amount of the substance of the nominal component in the chemical formula is dissolved in 300 ml of deionized water, and the chloride ion concentration in the mixed solution is controlled to be 10 mol / L; a mixed solution is obtained; (2) 300 ml of citric acid / ethylene glycol aqueous solution was mixed evenly with the above mixed solution, with the stirring speed being 500 r / min, the temperature being 35° C., and the time being 50 min, and the molar ratio of citric acid:ethylene glycol:metal salt being controlled to be 15:15:1, to obtain a sol ink mother liquor; (3) aging the above sol ink mother solution at room temperature for 60 hours to obtain a sol; (4) Add 5 L of deionized water to the above sol, add 56 g of gum arabic to adjust the atomization stability, stir evenly, stir at a speed of 500 r / min, a temperature of 35° C., and a time of 50 min, and adjust the viscosity to 18 cP to obtain a sol ink; (5) The above sol ink is atomized to form droplets, and the ultrasonic frequency is 2.5 MHz; the droplets are transported to the printing nozzle through the carrier gas, and the carrier gas, the constraining gas and the droplets together constitute an aerosol jet. The flow rate of the carrier gas is set to 450 sccm and the flow rate of the constraining gas is set to 100 sccm to control the width and injection speed of the aerosol jet. The aerosol jet is sprayed onto a 150° C. substrate through a 300° C. heating device, and the printing height is 8 mm. The solvent evaporation rate of the aerosol jet in the air is controlled, and the printing speed is set to 45 mm / s and the number of printing layers is 300 layers to control the oxidation process of the aerosol on the substrate to obtain oxide gel powder; nitrogen is used for both the carrier gas and the constraining gas; (6) annealing the oxide gel powder in a mixed atmosphere of hydrogen and argon (the volume ratio of hydrogen to argon is 5:95) to perform a reduction reaction at a reduction temperature of 700°C for 4 hours, and obtaining a micro-nano NdFeB permanent magnet material after cooling; (7) Disperse the micro-nano NdFeB permanent magnet material in tetrahydrofuran, sieve it with a nano-scale filter membrane, and continue to rinse until the filtrate is clear. After drying the filtrate at 90°C for 2 hours, the nano-scale NdFeB permanent magnet material is obtained.

[0043] Depend on Figure 6 It can be seen that the saturation magnetization intensity of the obtained nano-scale NdFeB permanent magnet material is 42.1emu / g, the residual magnetization intensity is 12.6emu / g, and the coercive force is 1896Oe.

[0044] Example 5: (1) Neodymium chloride hexahydrate, ferric chloride hexahydrate and boric acid were mixed according to Nd 15 Fe 77.5 B7.5 The amount of the substance of the nominal component in the chemical formula is dissolved in 200 ml of deionized water, and the chloride ion concentration in the mixed solution is controlled to be 6 mol / L; a mixed solution is obtained; (2) 200 ml of citric acid / ethylene glycol aqueous solution was mixed evenly with the above mixed solution, the stirring speed was 800 r / min, the temperature was 5°C, the time was 60 min, and the molar ratio of citric acid:ethylene glycol:metal salt was controlled to be 40:40:1, to obtain a sol ink mother liquor; (3) aging the above sol ink mother solution at room temperature for 36 hours to obtain a sol; (4) Add 4 L of deionized water to the above sol, add 4.4 g of polyethylene glycol to adjust the atomization stability, stir evenly, stir at a speed of 800 r / min, a temperature of 5° C., and a time of 60 min, and adjust the viscosity to 14 cP to obtain a sol ink; (5) The above sol ink is atomized to form droplets, and the ultrasonic frequency is 2.1 MHz; the droplets are transported to the printing nozzle through the carrier gas, and the carrier gas, the constraining gas and the droplets together constitute an aerosol jet. The flow rate of the carrier gas is set to 200 sccm and the flow rate of the constraining gas is set to 50 sccm to control the width and injection speed of the aerosol jet. The aerosol jet is sprayed onto a 180°C substrate through a 150°C heating device, and the printing height is 9 mm. The solvent evaporation rate of the aerosol jet in the air is controlled, and the printing speed is set to 50 mm / s and the number of printing layers is 500 layers to control the oxidation process of the aerosol on the substrate to obtain oxide gel powder; nitrogen is used for both the carrier gas and the constraining gas; (6) annealing the oxide gel powder in a mixed atmosphere of hydrogen and argon (the volume ratio of hydrogen to argon is 5:95) to perform a reduction reaction at a reduction temperature of 650°C for 3 hours, and obtaining a micro-nano NdFeB permanent magnet material after cooling; (7) Disperse the micro-nano NdFeB permanent magnet material in DMF, sieve it with a nano-scale filter membrane, and continue to rinse until the filtrate is clear. Dry the filtrate at 90°C for 0.5h to obtain the nano-scale NdFeB permanent magnet material.

[0045] Depend on Figure 7 It can be seen that the saturation magnetization intensity of the obtained nano-scale NdFeB permanent magnet material is 55.3emu / g, the residual magnetization intensity is 19.9emu / g, and the coercive force is 1931Oe.

[0046] Any matters not described in the present invention are applicable to the prior art.

Claims

1. A method for preparing nano-grade NdFeB permanent magnet material by aerosol jet printing technology, characterized in that: The method comprises the following steps: Step 1, dissolving a metal salt and boric acid in deionized water to obtain a mixed solution; the metal salt comprises neodymium chloride hexahydrate and ferric chloride hexahydrate; Step 2, uniformly mixing the citric acid / ethylene glycol aqueous solution with the mixed solution obtained in step 1 to obtain a sol ink mother solution; Step 3, aging the sol ink mother liquor obtained in step 2 to obtain a sol; Step 4, uniformly mixing the organic dispersant, deionized water and the sol obtained in step 3 to adjust the viscosity of the system, and then adjust the atomization stability of the sol to obtain a sol ink; Step 5, atomizing the sol ink obtained in step 4 to form droplets, and conveying them to an aerosol jet printing device; the droplets are conveyed to the printing nozzle by a carrier gas; the carrier gas, the constraining gas and the droplets together form an aerosol jet and are ejected from the printing nozzle; the aerosol jet is ejected onto the substrate through a heating device for aerosol jet printing to obtain oxide gel powder; Step 6, annealing the oxide gel powder obtained in step 5 in a mixed atmosphere of hydrogen and argon to perform a reduction reaction to obtain a micro-nano grade NdFeB permanent magnet material; Step 7: Disperse the micro-nano NdFeB permanent magnet material obtained in step 6 into an insoluble solvent, sieve it with a nano-scale filter membrane, continue to rinse until the filtrate is clear, and dry the filtrate to obtain the nano-scale NdFeB permanent magnet material.

2. The method for preparing nano-grade NdFeB permanent magnet material by aerosol jet printing technology according to claim 1, characterized in that: In step 1, the ratio of neodymium, iron and boron is as follows: 15 Fe 77.5 B 7.5 The amount of substance of the nominal component in the chemical formula is added; the chloride ion concentration is 3~10mol / L.

3. The method for preparing nano-grade NdFeB permanent magnet material by aerosol jet printing technology according to claim 1, characterized in that: In step 2, the molar ratio of citric acid, ethylene glycol and metal salt is 2-50:2-50:1; and the volume ratio of citric acid / ethylene glycol aqueous solution to the mixed solution is 1:

1.

4. The method for preparing nano-grade NdFeB permanent magnet material by aerosol jet printing technology according to claim 1, characterized in that: In step 3, the aging time is 12 to 72 hours, and the aging temperature is room temperature.

5. The method for preparing nano-grade NdFeB permanent magnet material by aerosol jet printing technology according to claim 1, characterized in that: In step 4, the volume ratio of deionized water to sol is 1-10:1-5, and the ratio of the mass of the organic dispersant to the volume of the sol is 1 g:100-1000 ml; In step 2 and step 4, the mixing is performed uniformly by stirring; the stirring process is: the speed is 100-1000 r / min, the temperature is 0-40° C., and the time is 10-60 min; In step 4, the viscosity of the sol ink is 1-20 cP.

6. The method for preparing nano-grade NdFeB permanent magnet material by aerosol jet printing technology according to claim 1 or 5, characterized in that: In step 4, the organic dispersant is one of polyvinyl alcohol, polyvinyl pyrrolidone, polyethylene glycol, polyacrylic acid or gum arabic.

7. The method for preparing nano-grade NdFeB permanent magnet material by aerosol jet printing technology according to claim 1, characterized in that: In step 5, the atomization process is ultrasonic atomization, and the ultrasonic frequency is 1.5-2.5 MHz.

8. The method for preparing nano-grade NdFeB permanent magnet material by aerosol jet printing technology according to claim 1, characterized in that: In step 5, the flow rates of the carrier gas and the confinement gas are changed to adjust the width and injection speed of the aerosol jet; the flow rate of the carrier gas is 200-500 sccm, and the flow rate of the confinement gas is 50-150 sccm; In step 5, the printing height and the temperature of the heating device are changed to regulate the solvent evaporation behavior of the aerosol jet in the air; the printing height is 5-10 mm, and the temperature of the heating device is 150-350° C.; In step 5, the printing speed, the number of printing layers and the temperature of the substrate are changed to control the oxidation process of the aerosol on the substrate; The printing speed is 5~50mm / s, the number of printing layers is 50~500 layers, and the temperature of the substrate is 40~180℃.

9. The method for preparing nano-grade NdFeB permanent magnet material by aerosol jet printing technology according to claim 1, characterized in that: In step 5, both the carrier gas and the confinement gas are nitrogen or an inert gas, and the inert gas is argon.

10. The method for preparing nano-grade NdFeB permanent magnet material by aerosol jet printing technology according to claim 1, characterized in that: In step 6, the reduction reaction temperature is 550-700°C and the time is 3-6 hours; In step 6, the volume ratio of hydrogen to argon is 1-25:75-99, and the sum of the volume ratios of the two is 100%; In step 7, the insoluble solvent is DMF, acetone or tetrahydrofuran; In step 7, the pore size of the nano-scale filter membrane is 0.05-0.22 μm; In step 7, the drying temperature is 60-100° C., and the drying time is 0.5-24 h.

Citation Information

Patent Citations

  • Method for preparing neodymium iron boron permanent magnetic nanoparticles

    CN103990808A

  • Production method of rare earth Nd<3+> ion imprinted composite membrane

    CN106423089A

  • Method for preparing neodymium iron boron magnetic powder through chemical method

    CN119132774A

  • Method for preparing high-performance copper-titanium alloy through aerosol jet printing technology

    CN119747678A

  • Method for manufacturing magnet and method for producing ultrafine particle magnetic powder used for it

    JP2005203653A